The externalities of fire sales: Evidence from collateralized loan obligations - Shohini Kundu (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2023)
This paper investigates how covenants, intrinsic to Collateralized Loan Obligation (CLO) indentures, may amplify idiosyncratic shocks, imposing negative externalities on unrelated firms in CLO portfolios. Following a negative shock to the oil & gas industry, CLOs with exposure to oil and gas loans are pushed closer to their covenant thresholds and fire-sell unrelated loans in the secondary loan market to alleviate these constraints. These fire sales exert price pressure on the securities of unrelated firms, creating market dislocations. The erosion in the liquidity positions of exposed firms spills over into real economic activity. The findings highlight the real effects from fire sales arising due to contracting frictions.
Keywords: E44; G23; E32; 330; covenants; contracting frictions; closed-end funds; fire sales; externalities; CLOs